Quantitative Analysis of corporate income taxation option for partnerships in Germany - Buschhaus, Matthias (Journal of Finance and Financial Law, 2025)
The purpose of the article. The aim of this article is to quantitatively analyse the taxation of partnerships in Germany. In doing so, this paper examines the quantitative effects of the new taxation system (so-called ‘option model’) for partnerships in Germany and answers the question of which factors influence the tax burden the most and whether the option model would have been more favourable for large partnerships in Germany in the past. Methodology. The methodology in this paper was a quantitative research within the framework of Pearson correlations of selected microdata, which was provided by the ‘Stiftung Familienunternehmen’ (Foundation for Family Businesses) and includes the partnerships with the highest number of employees in Germany in the years 2010–2018. Results of the research. The results of this paper are, in particular, the amount of withdrawals from the partnership under the option model introduced on 1 January 2022 can be decisive for the tax expense. Furthermore, it was found that the option model would not have led to a lower tax expense for the largest partnerships in Germany in the past.